The effect of swimsuit resistance on freestyle swimming race time - Webb, A. P.; Taunton, D. J.; Hudson, D. A.; Forrester, A. I. J.; Turnock, S. R. (Procedia Engineering, 2014)
It is known that swimming equipment (suit, cap and goggles) can affect the total resistance of a swimmer, and therefore impact the resulting swimming speed and race time. After the 2009 swimming world championships (WC) the international swimming federation (FINA) banned a specific type of full body suit, which resulted in an increase in race times for subsequent WC events. This study proposes that the 2009 suits provided a reduction in swimming resistance and aims to quantify this resistance reduction for male and female freestyle events. Due to the practical difficulties of testing a large sample of swimmers a simulation approach is adopted. To quantify the race time improvement that the 2009 suits provided, an equivalent 2009 "no-suit" dataset is created, incorporating the general trend of improving swimming performance over time, and compared to the actual 2009 times. A full race simulation is developed where the start, turn, underwater and surface swimming phases are captured. Independent resistance models are used for surface and underwater swimming; coupled with a leg propulsion model for underwater undulatory swimming and freestyle flutter kick, and a single element arm model to simulate freestyle arm propulsion. A validation is performed to ensure the simulation captures the change in swimming speed with changes to resistance and is found to be within 5% of reality. Race times for an equivalent "no-suit" 2009 situation are simulated and the total resistance reduced to achieve the actual 2009 race times. An average resistance reduction of 4.8% provided by the 2009 suits is identified. A factor of 0.47 ± 10%, to convert resistance changes to freestyle race time changes is determined.